One day at a time : children living with leukemia - Bergman, Thomas, 1947- (Milwaukee : Gareth Stevens Children's Books, 1989)
Focuses on children with leukemia and follows them as they are treated for their illness.
Includes bibliographical references (p. 54).
Keywords: Leukemia in children; Leukemia